Electroanalysis of urinary L-dopa using tyrosinase immobilized on gold nanoelectrode ensembles - Pinho, Ana (2012)
The performance of an amperometric biosensor constructed by associating tyrosinase (Tyr) enzyme with the advantages of a 3D gold nanoelectrode ensemble (GNEE) is evaluated in a flow-injection analysis (FIA) system for the analysis of l-dopa. GNEEs were fabricated by electroless deposition of the metal within the pores of polycarbonate track-etched membranes. A simple solvent etching procedure based on the solubility of polycarbonate membranes is adopted for the fabrication of the 3D GNEE. Afterward, enzyme was immobilized onto preformed self-assembled monolayers of cysteamine on the 3D GNEEs (GNEE-Tyr) via cross-linking with glutaraldehyde. The experimental conditions of the FIA system, such as the detection potential (−0.200 V vs. Ag/AgCl) and flow rates (1.0 mL min−1) were optimized. Analytical responses for l-dopa were obtained in a wide concentration range between 1 × 10−8 mol L−1 and 1 × 10−2 mol L−1. The limit of quantification was found to be 1 × 10−8 mol L−1 with a resultant % RSD of 7.23% (n = 5). The limit of detection was found to be 1 × 10−9 mol L−1 (S/N = 3). The common interfering compounds, namely glucose (10 mmol L−1), ascorbic acid (10 mmol L−1), and urea (10 mmol L−1), were studied. The recovery of l-dopa (1 × 10−7 mol L−1) from spiked urine samples was found to be 96%. Therefore, the developed method is adequate to be applied in the clinical analysis.